Cinema of confinement (2019)
Since the birth of cinema, filmmakers have explored different ways of telling stories across multiple settings within the length of one film. From the early editing experiments of Edwin S. Porter and D. W. Griffith, to the current globe- trotting of James Bond and Marvel movies, shifts in location continue to fascinate filmmakers and audiences alike. Aesthetically, many of these movies articulate cinematic space as fluid and continuous, since the image is subordinated to the narrative even when the story changes locations. As such, the mode of production for the classic style of narration is to naturalize and integrate space by not drawing significant attention to the mechanisms that create the illusion of cinematic reality. This process is often referred to as the invisible style of narration, which involves composing and editing space that directs the viewer’s spectatorship towards the narrative and the actions of the characters. These films offer the spectator a cinema that displays the unlimited power of the camera, showing all perspectives of the events throughout a variety of settings.